Pengembangan Media Pembelajaran Interaktif (Ispring Quizmaker) Pada Materi Bahasa Indonesia Kelas V SD Negeri 1 Sambijajar - Putri Alwi Rahayu; Nugrananda Janattaka (Departement of Mathematics Education, 2024)
Educators in the era of society 5.0, teachers must have skills in the digital field and think creatively. Director of Hafecs (Highly Functioning Education Consulting Services) assesses that in the era of society 5.0 (society 5.0) teachers are required to be more innovative and dynamic in teaching in the classroom. dynamic in teaching in the classroom. This research utilizes the Analysis, Design, Development, and This research uses the Analysis, Design, Development, Implementation, Evaluation, development model. (ADDIE). The level of validity is determined from the validation of material experts, media experts, and media experts. validation of material experts, media experts, and linguists. Media expert validation 87%, Material expert validation 86%, Language expert validation 86%, so that it can be concluded “Very Valid”. Assessment of applicability is taken from the teacher response questionnaire to get a score of 92% and small-scale student response to get a score of 87% and small-scale student response to get a score of 87%. get a score of 87% and large-scale student responses get 90% so that the level of applicability is declared “very valid”. level is declared “very valid”